A phosphine-based redox method for direct conjugation of disulfides. Issue 89 (24th October 2022) - Lu, Yong; You, Lin; Chen, Chuo
Abstract : Redox-assisted Disulfide Direct Conjugation (RDDC) allows for disulfide functionalization under mild aqueous conditions without prior reduction. Abstract : Technologies for cysteine disulfide detection and conjugation are pivotal to understanding protein functions and developing disulfide-derived therapeutic agents. Currently, disulfide modification requires reductive cleavage prior to functionalization, posing challenges to differentiating disulfides from free thiols. We describe herein Redox-assisted Disulfide Direct Conjugation (RDDC) as a new method to enable disulfide rebridging without cross-reacting with free thiols.